An analysis of potato consumption habits and diet quality among adults and children in the UK. Issue 3 (23rd August 2015) - Gibson, S.; Francis, L.
Abstract: Many people are confused about the nutritional role of potatoes in a healthy, balanced diet. Starchy foods are often under‐regarded by the public and maligned by proponents of low carbohydrate diets, yet carbohydrate should supply around 50% of dietary energy, preferably from sources such as potatoes, pulses and wholegrains. Potatoes provide significant quantities of shortfall micronutrients, yet they do not count as vegetables in 5 A DAY targets. To provide balanced advice, research is needed on potato consumption and its possible nutritional consequences. Therefore we analysed individual dietary records from the N ational D iet and N utrition S urvey 2008–2012 to investigate potato consumption patterns and associations with nutrient intakes. We hypothesised that high consumption of potatoes would be associated with higher total intakes of potassium, B vitamins and fibre. Across the whole population, potatoes provided 7% of energy, 15% of potassium, 13% of dietary fibre (non‐starch polysaccharide) and vitamin C, 14% of vitamin B6, 10% of folate, 8% of magnesium and 6% of iron. Both very low and very high consumption of potatoes (Q1 and Q5) was associated with lower energy and nutrient intakes, compared with average consumers. Lower micronutrient intakes were most pronounced in Q5 (mean 14.8% energy from potatoes), although Q1 had lowest intakes of potassium, vitamin B6 and thiamin. Food intakes suggest a less healthy, varied dietary pattern among high potato consumers. Conversely, low consumers of potatoes had lower intakes of potassium, thiamin and vitamin B6 (all found in potatoes) despite an apparently health‐conscious dietary pattern that included higher consumption of fruit, vegetables and fish. Our study suggests that based on current habits, a broad range of potato consumption is compatible with good nutrition, while high reliance on potatoes may be associated with an unbalanced diet. To help raise intakes of shortfall nutrients such as potassium and fibre, consumption of potatoes could be encouraged alongside existing healthy eating messages relating to vegetables, fruit and wholegrain foods.